Development of Qurdio as a Media for Learning Al Qur'an Hadith for Class IX Students of MTs Nizhamiyah Ploso - Istikomah Istikomah; Rohmat Hidayat; Faridl Darmawan (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to develop learning media in the form of video animation. For the presentation of the material using the subjects of Al-Qur'an Hadith, class IX students of Mts Nizhamiyah Ploso. The development of learning media using the Kinemaster Application as a medium for making video animations of the Qur'an Hadith. The learning media trial was conducted by class IX students of Mts Nizhamiyah Ploso with a small group trial of 5 students, and a large group trial of 25 students. This research method uses development research which is usually abbreviated as R&D, by applying several stages, namely first potential and problem analysis, second data collection, third product design, fourth design validation, fifth design improvement, sixth product trial, seventh product revision. The results of trials and product feasibility conducted by students and validators. Feasibility of the product obtained a score of 77.78% from media experts, and product feasibility from material experts obtained a score of 74.06%. The small group trial obtained an average score of 72%, and the large group obtained an average score of 75%. Based on these results, it can be concluded that the learning media in the form of video animation is very interesting and suitable to be used to help students learn in class IX Mts Nizhamiyah Ploso.